Cardiovascular Indicators of Systemic Circulation and Acute Mountain Sickness: An Observational Cohort Study - Chen, Renzheng; Sun, Mengjia; Yang, Jie; Liu, Chuan; Zhang, Jihang; Ke, Jingbin; Deng, Yuhan; He, Chunyan; Yang, Yuanqi; Cheng, Ran; Yuan, Fangzhengyuan; Tan, Hu; et al. (Frontiers in Physiology, 2021)
Background: Acute high altitude (HA) exposure results in blood pressure (BP) and cardiac function variations in most subjects, some of whom suffer from acute mountain sickness (AMS). Several previous studies have found that cardiovascular function indicators are potentially correlated with AMS. Objectives: This study aimed to examine HA-induced cardiovascular adaptations in AMS patients and compare them with healthy subjects. We also aimed to investigate the relationship between cardiovascular function indicators and AMS, as well as to provide some insightful information about the prevention and treatment of AMS. Methods: Seventy-two subjects were enrolled in this cohort study. All the subjects ascended Litang (4100 m above sea level). They were monitored by 24-hour ambulatory blood pressure device and underwent echocardiography examination within 24 hours of altitude exposure. The 2018 Lake Louise questionnaire was used to evaluate AMS. Results: AMS group consisted of more women (17 [60.7%] vs. 10 [22.7%], P=0.001) and fewer smokers (5 [17.9%] vs.23 [52.3%], P=0.003). Compared with subjects without AMS, subjects with AMS had lower pulse pressure (PP) (daytime PP, 45.23±7.88 vs 52.14±4.75, P<0.001; nighttime PP, 42.81±5.92 vs 49.39±7.67, P<0.001) and lower effective arterial elastance (Ea) (1.53±0.24 vs 1.73±0.39, P=0.023). Multivariate regression indicated that female sex (OR=0.23, P=0.024), lower daytime PP (OR=0.86, P=0.004) and lower Ea (OR=0.03, P=0.015) at low altitude (LA) were independent risk factors for AMS. Combined daytime PP and Ea at LA had a high predictive value for AMS (AUC=0.873; 95% CI, 0.789–0.956). Correlation analysis showed that AMS-induced headache correlated with daytime PP (R= -0.401, P<0.001) and nighttime PP at LA (R= -0.401, P<0.001). Conclusions: Our study demonstrated that AMS patients had a lower PP and Ea at LA. These baseline indicators of vasodilation at LA were closely associated with AMS, which may explain the higher headache severity in subjects with higher PP at LA.